Pulse oximetry and oxygen services for the care of children with pneumonia attending frontline health facilities in Lagos, Nigeria (INSPIRING-Lagos): study protocol for a mixed-methods evaluation. Issue 5 (2nd May 2022) - Graham, Hamish R; Olojede, Omotayo E; Bakare, Ayobami Adebayo A; McCollum, Eric D; Iuliano, Agnese; Isah, Adamu; Osebi, Adams; Seriki, Ibrahim; Ahmed, Tahlil; Ahmar, Samy; Cassar, Christine; Valentine, Paula; et al.
Abstract : Introduction: The aim of this evaluation is to understand whether introducing stabilisation rooms equipped with pulse oximetry and oxygen systems to frontline health facilities in Ikorodu, Lagos State, alongside healthcare worker (HCW) training improves the quality of care for children with pneumonia aged 0–59 months. We will explore to what extent, how, for whom and in what contexts the intervention works. Methods and analysis: Quasi-experimental time-series impact evaluation with embedded mixed-methods process and economic evaluation. Setting: seven government primary care facilities, seven private health facilities, two government secondary care facilities. Target population: children aged 0–59 months with clinically diagnosed pneumonia and/or suspected or confirmed COVID-19. Intervention: 'stabilisation rooms' within participating primary care facilities in Ikorodu local government area, designed to allow for short-term oxygen delivery for children with hypoxaemia prior to transfer to hospital, alongside HCW training on integrated management of childhood illness, pulse oximetry and oxygen therapy, immunisation and nutrition. Secondary facilities will also receive training and equipment for oxygen and pulse oximetry to ensure minimum standard of care is available for referred children. Primary outcome: correct management of hypoxaemic pneumonia including administration of oxygen therapy, referral and presentation to hospital. Secondary outcome: 14-day pneumonia case fatality rate. Evaluation period: August 2020 to September 2022. Ethics and dissemination: Ethical approval from University of Ibadan, Lagos State and University College London. Ongoing engagement with government and other key stakeholders during the project. Local dissemination events will be held with the State Ministry of Health at the end of the project (December 2022). We will publish the main impact results, process evaluation and economic evaluation results as open-access academic publications in international journals. Trial registration number: ACTRN12621001071819; Registered on the Australian and New Zealand Clinical Trials Registry.